Are Emotions Embodied Evaluative Attitudes? Critical Review of Julien A. Deonna and Fabrice Teroni’s The Emotions: A Philosophical Introduction - Smith, Joel (2016)
Deonna and Teroni’s The Emotions is both an excellent introduction to philosophical work on emotions and a novel defence of their own Attitudinal Theory. After summarising their discussion of the literature I describe and evaluate their positive view. I challenge their theory on three fronts: their claim that emotions are a form of bodily awareness, their account of what makes an emotion correct, and their account of what justifies an emotion.